Eksistensi Budaya Pappaseng Sebagai Sarana Pendidikan Moral - Dewi Handayani; Sunarso Sunarso (Institut Seni Indonesia Denpasar, 2020)
This study aims to analyze the importance of the existence of Pappaseng culture as a moral education suggestion for young people so that they have character and wise attitudes and behaviors in the midst of globalization. Pappaseng is a traditional literary work which is a work of art that uses language as a medium in presentation, passed down from generation to generation as a will in the Bugis tribe. The method in this research uses a qualitative approach with ethnographic design. Research subjects were sixteen South Sulawesi female student dormitories in Yogyakarta. Data collection techniques through in-depth interviews and literature study. The research results show that the development of the times has made Pappaseng's values ​​gradually eroded in some individuals, but there are still many people who still maintain Pappaseng culture because it is a life guide inherited from ancestors and the values ​​contained in Pappaseng culture are relevant to the values Islam. The importance of culture-based education because it can improve the quality of human life such as Pappaseng which can be used as a means of moral education and character building for humans. Keywords : Culture, Pappaseng, Moral Education